FAKTOR-FAKTOR TERJADINYA KEMATIAN NEONATAL DI INDONESIA (ANALISIS DATA SDKI 2017) - Mochtar Ghaffar Ramadhan (2021)
Neonatal mortality is a problem that must be resolved in the SDGs. Likewise in Indonesia, there is still a gap between the RPJMN 2020-2024 targets to reduce the neonatal mortality rate to 10 per 1000 live births. This study aims to determine the factors of neonatal mortality in Indonesia as one way to achieve the target of the RPJMN. This study used a cross-sectional study design with secondary data analysis of the IDHS 2017. The sample used in this study was 34,972 women aged 15-49 years old who had given birth after applied the weighted setting analysis. The analysis used in this research is spatial analysis, Chi-Square, and multiple logistic regression. The results of the bivariate analysis showed that there was a relationship between socio-economic factors (maternal occupation and wealth status), maternal factors (maternal age, parity, birth interval, and delivery complications), infant factor (birth weight) and health services factors (antenatal visit and delivery assistance) with the neonatal death. The results of multivariate analysis showed that the low birth weight (p = 0.000; POR = 12.58; 95% CI 8.07-19.63), parity (p = 0.001; POR = 2.29; 95% CI 1.38-3.80) and maternal occupation (p = 0.002; POR = 2.11; 95% CI 1.32-3.36) were included in the multivariate final model. The conclusion of this study states that LBW is the most influential variable on the incidence of neonatal death in Indonesia.